Generation of a pdmH1N1 2018 Influenza A Reporter Virus Carrying a mCherry Fluorescent Protein in the PA Segment - Bu, Ling; Chen, Boqian; Xing, Lei; Cai, Xuejun; Liang, Shuhua; Zhang, Liying; Wang, Xinhua; Song, Wenjun (Frontiers in Cellular and Infection Microbiology, 2022)
Influenza A virus (IAV) is a major human pathogen associated with significant morbidity and mortality worldwide. Through serial passage in mice, we generated a recombinant pdmH1N1 2009 IAV, A/Guangdong/GLW/2018 (GLW/18-MA), which encodes an mCherry gene fused to the C-terminal of a polymerase acidic (PA) segment and demonstrated comparable growth kinetics to the wild-type. Nine mutations were identified in the GLW/18-MA genome: PA (I61M, E351G, and G631S), NP (E292G), HA1 (T164I), HA2 (N117S and P160S), NA (W61R), and NEP (K44R). The recombinant IAV reporter expresses mCherry, a red fluorescent protein, at a high level and maintains its genetic integrity after five generations of serial passages in Madin-Darby Canine Kidney cells (MDCK) cells. Moreover, the imaging is noninvasive and permits the monitoring of infection in living mice. Treatment with oseltamivir or baicalin followed by infection with the reporter IAV led to a decrease in fluorescent protein signal in living mice. This result demonstrates that the IAV reporter virus is a powerful tool to study viral pathogenicity and transmission and to develop and evaluate novel anti-viral drugs, inhibitors, and vaccines in the future.